Students’ Reading Comprehension Problem in Reading Analytical Exposition Text in SMAN 1 Solok - Yunita Hutabarat; Yetti Zainil (Journal of English Language Teaching, 2020)
This study is aimed to find out students’ reading comprehension problem in reading analytical exposition text in SMAN 1 SOLOK. This study was conducted through descriptive quantitative method. The sample of this study was 30 students taken from class which got the lowest score in English subject according to pre-luminary research and interview with English teacher. Furthermore, the data were collected by using reading comprehension test and questionnaire. The finding of this study indicates that 65, 65% students face difficulties in comprehending analytical exposition text. Therefore, factors affecting the difficulties are general ability of English (448,04%), students’ learning interest towards English (47,32%), learning motivation (46,59%), students preparation (49,07%), availability of sources (32,15%), and  students environment (41,67%).